Interactive apeaking activities to strengthen oral interaction and accurate Wh-question intonation in A1 EFL students - Paucar Sangoquiza, Verónica Pilar (2021)
For many years, students try to learn English as a foreign language since they are kids until they become adults in Ecuador, but the speaking abilities are not developed in an effective way because the students are exposed to mechanical drills where they do not acquire the English language in order to be used as a tool to establish oral communication. I decided to apply this research due to the lack of oral interaction and intonation in wh-questions during the English class process. This project was focused on A1 level - eight graders- of a private high school in Quito where there are students with difficulties when they attempt to communicate their thoughts or ideas which need to be solved in order to strengthen the oral interaction. In order to succeed in this project, video recordings, teacher’s observation and a survey were used to show that interactive speaking activities such as a video, a game and a song help them speak, participate, have fun and interact during the teaching process. In addition, they felt relaxed, motivated and excited when they had to work in pairs or groups.